Implementation of a Parent Training Program During Community-Based Dissemination (From In-Person to Hybrid): Mixed Methods Evaluation - Heather McGrane Minton; Linda Murray; Marjorie J Allan; Roslyn Perry; Amie F Bettencourt; Deborah Gross; Lauri Strano; Susan M Breitenstein (JMIR Publications, 2024)
BackgroundParent training interventions support and strengthen parenting practices and parent-child relationships and improve child behavior. Between March 2018 and February 2020, a community-based parenting program conducted 38 in-person Chicago Parent Program (CPP) groups. In response to the COVID-19 pandemic, we modified the delivery of the in-person CPP to hybrid delivery using the self-administered, web-based version of the CPP (ezParent) paired with web-based, videoconferenced group sessions. ObjectiveThis study aims to describe the delivery transition and implementation outcomes of the hybrid delivery of the CPP (ezParent+group) during community-based dissemination. MethodsThis single-group, mixed methods retrospective evaluation examined the implementation outcomes using the RE-AIM (Reach, Efficacy, Adoption, Implementation, and Maintenance) framework. We report on data from hybrid ezParent delivery between September 2020 and August 2022. Parents completed pre- and postprogram surveys that included motivation to participate and perceived changes in parent-child behavior. Digital analytics captured ezParent completion. Facilitators completed fidelity assessments and participated in postintervention interviews. ResultsIn total, 24 hybrid ezParent groups (n=240 parents) were delivered by 13 CPP-trained facilitators. Parents reported high levels of satisfaction with the program and improvements in their feelings of parenting self-efficacy and their child's behavior following their participation in hybrid ezParent. On average, parents completed 4.58 (SD 2.43) 6 ezParent modules. The average group attendance across the 4 sessions was 71.2%. Facilitators found the hybrid delivery easy to implement and reported high parent engagement and understanding of CPP strategies. ConclusionsUsing the hybrid ezParent intervention is a feasible and effective way to engage parents. Lessons learned included the importance of academic and community-based organization partnerships for delivering and evaluating robust programs. Implementation facilitators and barriers and future research recommendations are discussed.